2021
DOI: 10.2147/ijn.s278885
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles Combined with Cytosine Arabinoside Show Anti-Leukemia Stem Cell Effects on Acute Myeloid Leukemia by Regulating Reactive Oxygen Species

Abstract: Background and Aim Acute myeloid leukemia (AML), initiated and maintained by leukemia stem cells (LSCs), is often relapsed or refractory to therapy. The present study aimed at assessing the effects of nanozyme-like Fe 3 O 4 nanoparticles (IONPs) combined with cytosine arabinoside (Ara-C) on LSCs in vitro and in vivo. Methods The CD34 + CD38 – LSCs, isolated from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In recent years, nanoparticles are known as novel antioxidants that protect against some oxidative stress damage [43]. Metal-based nanoparticles including iron oxide have beneficial roles in management of diseases regarding their antioxidant effects [44,45]. In the present study the antioxidant role of ferric oxide nanoparticles against isoniazid induced neurotoxicity was studied via the evaluation of several markers of the oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, nanoparticles are known as novel antioxidants that protect against some oxidative stress damage [43]. Metal-based nanoparticles including iron oxide have beneficial roles in management of diseases regarding their antioxidant effects [44,45]. In the present study the antioxidant role of ferric oxide nanoparticles against isoniazid induced neurotoxicity was studied via the evaluation of several markers of the oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…Even though acute myeloid leukemia (AML) principally affects elderly [ 2 ], it represents the 20% of childhood leukemia cases [ 1 ]. The most relevant aspect of pediatric AML remains the poor prognosis [ 26 ] with a long-term survival rate around the 50% [ 27 ], when patients are properly treated.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) represents the 20% of total childhood leukemia diagnoses [ 1 ], even though it remains the most frequent type of acute leukemia in the elderly [ 2 ]. In 0–2 year-old children, this kind of leukemia is characterized by poor prognosis, with a survival rate around the 60% [ 3 ], and high treatment-related toxicity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… Dou et al (2021) found that the combination of Fe 3 O 4 nanoparticles with cytarabine (Ara-C) inhibited leukemia stem cell (LSC) more than Ara-C alone. They analyzed changes in ROS-related substances such as gp91-phox and SOD1 by measuring ROS levels in LSC and non-LSC under different conditions.…”
Section: Application Of Iron Nanoparticles In Leukemiamentioning
confidence: 99%